Endoscopic total parathyroidectomy via anterior chest approach with forearm autotransplantation for secondary hyperparathyroidism: a comparison of surgical results with open total parathyroidectomy with autotransplantation - Hua, Tebo; Lou, Jinfeng; Zhu, Ye; Luo, Yong; Zhang, Hai; Yang, Jiahui (Frontiers in Oncology, 2023)
Objective: The purpose of this paper was to evaluate the clinical value of performing an endoscopic total parathyroidectomy through anterior chest approach with autotransplantation (EACtPTx+AT) in treating secondary hyperparathyroidism (SHPT) and to summarize and share the clinical experience； Methods: 24 patients with SHPT were retrospectively analyzed:11 patients underwent open total parathyroidectomy with autotransplantation(OtPTx+AT Group),and 13 patients underwent endoscopic parathyroidectomy through anterior chest approach with autotransplantation (EACtPTx+AT Group).Comparing the two groups regarding the following factors: (1)operating conditions, such as the blood loss during the operation, the length of time spent on the operating table, and the number of parathyroid glands removed ,postoperative drainage volume,hospital stay; (2) clinical efficacy ：parathyroid hormone (PTH) and serum calcium (Ca) levels;(3) postoperative complications。 Results: First,there were no significant differences in the number of parathyroid gland resection, operation time, intraoperative blood loss and hospital stay between the two groups. While,there were significant differences in postoperative drainage volume between the two groups.Second,the preoperative PTH and preoperative serum calcium of the two groups decreased significantly compared with that of the two groups after surgery, and there was a statistically significant difference. Thirdly,there was no postoperative bleeding, hoarseness or choking in the two groups, and no conversion to open surgery case in EACtPTx+AT group. Conclusion: Endoscopic treatment of SHPT using the anterior chest approach with forearm autotransplantation is significant improvements in clinical symptoms and lower levels of PTH and serum calcium after the operation. The results confirm the operation's safety and effectiveness.